Antenatal corticosteroids and incidence of neonatal respiratory distress after elective caesarean section in late preterm and term neonates - Aida de la Huerga López; Marta Sendarrubias Alonso; Ana Paola Jiménez Jiménez; Vanesa Matías del Pozo; Cristina Álvarez Colomo; María Fe Muñoz Moreno (Elsevier, 2019)
Introduction: Birth by elective caesarean section in late preterm and early term newborn increases the risk of respiratory distress. Administration of antenatal corticosteroids in these cases could reduce the respiratory distress and its severity. Objectives: To determine the influence of antenatal corticosteroids use in elective caesarean sections in the respiratory distress of the newborn from 35+0 to 38+6 weeks of gestational age. Patients and methods: Retrospective analytical study of caesarean sections from 35+0 to 38+6 gestational age was conducted in a tertiary hospital from January 2013 to April 2017. Data were collected from medical records of pregnant women and newborns after an implementation of new protocol of betamethasone administration to these elective caesarean sections. Analysis was performed on 2 newborn subgroups: preterm newborn (PTN) 35-36 gestational age and term (TN) 37-38 weeks. Results: A total of 208 elective caesarean sections were performed in the study period. Corticosteroids were administered in 97 (46.6%) of cases. The percentage of respiratory distress was higher in the group of preterm newborn compared to term newborn (29% vs. 8.8%, P < .001) and in term newborn higher at a lower gestational age. Between treated with corticosteroids or not, no significant differences were found in the treated and non-treated in the development of respiratory distress (PTN 30 vs. 30%, TN 9.1 vs. 6.9%, P = .6). Conclusions: No statistically significant differences were found in this study in favour of the administration of an antenatal dose of betamethasone in the reduction of respiratory distress in the elective caesarean sections from 35+0 to 38+6 gestational age. The delay in the indication of elective caesarean sections, whenever possible, could help reduce the incidence of newborn respiratory distress. Resumen: Introducción: El nacimiento por cesárea programada de los recién nacidos pretérmino tardíos y a término precoces aumenta el riesgo de distrés respiratorio. La administración de corticoides antenatales en estos casos podría disminuir el distrés respiratorio y su gravedad. Objetivos: Determinar la repercusión del uso de corticoides antenatales en las cesáreas programadas en el distrés respiratorio del recién nacido de 35 a 38+6 semanas de edad gestacional (SEG). Pacientes y métodos: Estudio analítico retrospectivo en un hospital de tercer nivel, de las cesáreas de 35+0 a 38+6 SEG desde enero de 2013 hasta abril de 2017. Recogida de datos de las historias clínicas de las gestantes y recién nacidos tras la instauración de un nuevo protocolo de administración de una dosis de betametasona a las gestantes con cesáreas programadas de esta edad gestacional. Análisis en 2 subgrupos: recién nacidos pretérmino (RNPT) 35-36 SEG y a término (RNT) 37-38 SEG. Resultados: En este periodo se realizaron 208 cesáreas programadas. Se administraron corticoides en 97 casos (46,6%). El porcentaje de distrés fue mayor en el grupo de cesáreas programadas de RNPT comparado con los RNT (29 vs. 8,8%; p < 0,001) y entre los RNT fue mayor a menor edad gestacional. Entre las cesáreas programadas tratadas y no tratadas con corticoides no se encontraron diferencias significativas en cuanto al desarrollo de distrés respiratorio (RNPT 30 vs. 30%; p = 1; RNT 9,1 vs. 6.9%; p = 0,6). Conclusiones: En este estudio no se encontraron diferencias estadísticamente significativas a favor del beneficio de la administración de una dosis antenatal de betametasona en la disminución del distrés respiratorio del recién nacido en las cesáreas programadas de 35+0 a 38+6 SEG. El retraso en la indicación de cesáreas programadas, siempre que sea posible, podría contribuir a disminuir la incidencia de distrés respiratorio.